Seven promises of a promise keeper - Trout, Mike. (Colorado Springs, CO : Focus on the Family, 1994)
Presents ideas of leading authors like Bill Bright, Dr. James Dobson, Jack Hayford, Howard Hendricks, and Gary Smalley on how men can cultivate deep, life-changing relationships with their wives, children, friends, churches, and the Lord.
In container (18 cm.).
Read by Mike Trout.
Keywords: Spiritual life -- Christianity; Christian life